Heterogeneous Layoff Effects of the US Short-Time Compensation Program - Marlon R. Tracey; Solomon Polachek (Institute of Labor Economics (IZA), 2018)
The Short-Time Compensation (STC) program enables US firms to reduce work hours via pro-rated Unemployment Insurance (UI) benefits, rather than relying on layoffs as a cost-cutting tool. Despite the program's potential to preclude skill loss and rehiring/ retraining costs, firms' participation rates are still very low in response to economic downturns. Using firm-level UI administrative data, we show why by illustrating which type firms benefit from the program and which do not. Semiparametric estimation indicates STC reduces layoff rates for cyclically sensitive firms by about 15%, but has no effect for more cyclically stable firms.
Keywords: C21; C38; J63; J65; 330; short-time compensation; layoffs; inverse probability weighting; heterogeneity; finite mixture model